RADIOGRAPHIC CHANGES IN HAND AND WRIST OF THE PATIENTS WITH EARLY RHEUMATOID ARTHRITIS AT REMISSION: A ONE YEAR FOLLOW-UP STUDY - Mahir Uğur; Kazım Şenel; Kadir Yıldırım; Selami Suma (Archives of Rheumatology, 2001)
This study was carried out with the aim of determining the relationship between disease activation and radiographic progression in early rheumatoid arthritis (RA) and determining whether radiographic progression continues in hand and wrist joints of the patients at remission period throughout one year. In 45 patients with early active RA, hand and wrist radiographies were determined with Larsen Dale method in the activation phase and after a year of remission. Patients were treated with low-dose prednisolone (7.5mg/day) and disease-modifying antirheumatic drugs (methotrexate and/or sulphasalasine). Erythrocyte sedimentation rate (ESR), C-reactive protein (CRP) and Ritchie Articular Index (RAI), indicators of disease activation, were recorded at routine follow-ups carried out in every month for a year, and annual means of these parameters were cummulatively (using time-integration) calculated. One year later, 36 patients went on remission during one year were evaluated. A significant change was obtained among Larsen scores of hand and wrist radiographies at onset and at the end of one year (p<0.01). Significant correlations were found between Larsen score at the onset and initial ESR (r = 0.32, p<0.05), initial CRP (r = 0.44, p<0.01) and initial RAI (r = 0.42, p<0.01) values. There was no significant correlation between the changes of Larsen scores and time-integrated parameters (p>0.05). In conclusion, we found that increased disease activation could be an indicator of the radiographic progression rate and that joint damage continued even at remission period throughout one year follow-up period.